2001
DOI: 10.1007/s004250100524
|View full text |Cite
|
Sign up to set email alerts
|

Changes in apoplastic pH and membrane potential in leaves in relation to stomatal responses to CO 2 , malate, abscisic acid or interruption of water supply

Abstract: Low CO2 concentrations open CO2-sensitive stomata whereas elevated CO2 levels close them. This CO2 response is maintained in the dark. To elucidate mechanisms underlying the dark CO2 response we introduced pH- and potential-sensitive dyes into the apoplast of leaves. After mounting excised leaves in a gas-exchange chamber, changes in extracellular proton concentration and transmembrane potential differences as well as transpiration and respiration were simultaneously monitored. Upon an increase in CO2 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 26 publications
3
54
1
1
Order By: Relevance
“…Furthermore, malate induces stomata closure in epidermal strips of fava bean (Vicia faba) with a half maximal concentration of 0.3 mM. In good agreement with these results, feeding malate to excised leaves reduces the transpiration rate in a dose-dependent manner (Hedrich et al, 2001). However, even at the highest concentration of malate used (40 mM), stomata still responded to CO 2 in the atmosphere, indicating that guard cells must have at least one additional CO 2 sensing system.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, malate induces stomata closure in epidermal strips of fava bean (Vicia faba) with a half maximal concentration of 0.3 mM. In good agreement with these results, feeding malate to excised leaves reduces the transpiration rate in a dose-dependent manner (Hedrich et al, 2001). However, even at the highest concentration of malate used (40 mM), stomata still responded to CO 2 in the atmosphere, indicating that guard cells must have at least one additional CO 2 sensing system.…”
Section: Discussionsupporting
confidence: 64%
“…One such event could be a change in the membrane potential. Reports have shown that decreases in [CO 2 ] cause hyperpolarization, whereas increases in [CO 2 ] cause depolarization of the guard cell plasma membrane (11,14,15,53). Low CO 2 -induced hyperpolarization would activate voltage-gated K ϩ influx channels (54) and provide the driving force for K ϩ uptake, contributing to stomatal opening (55).…”
Section: Discussionmentioning
confidence: 99%
“…We used leaf fragments floating on buffer solution and found that stomata closed halfway at 60 min after ABA application. In gas exchange experiments using intact leaves, stomatal conductance reached halfway 10 to 15 min after ABA application (Hedrich et al, 2001), and guard cells of intact leaf and epidermal peels were found to differ in calcium dynamics (Levchenko et al, 2008). In addition, many other factors, including pH of the extracellular space, oxygen availability, and hydrodynamics, may vary, causing the difference in the speed of the change.…”
Section: Discussion Vacuolar Acidification Is Necessary For the Rapidmentioning
confidence: 99%